IMPACT OF RECIDIVISTIC YOUTH ON THEIR LIFE AND THEIR FAMILY - Regi Jacob; Malviya, Anil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of a jail sentence in criminal law is to serve as a deterrent to the convicted criminal. An offender receives punished so that they may be rehabilitated and given a second chance at life in society in order to recoup the benefits of their criminal behaviour. In spite of the fact that there are no internationally agreed-upon standards for reporting recidivism, the rate of recidivism among criminals has been rising worldwide, and India gives a severely distorted image of that rate. Because of the fundamental role that incarceration plays in defining an offender’s trajectory and potential responses, research on recidivism and its connections to incarceration is essential. This article aims to objectively examine the global trends of repeat offenders, their motivations for reoffending, the degree to which these factors are linked, and what can be done to reduce recidivism everywhere. It will also examine some successful approaches used in other countries.